Dental anomalies and muscle segment homeobox 1 (MSX1) gene polymorphism in non-syndromic cleft lip with or without palate children - Elgali, Amel Elduhman (2016)
Non-syndromic cleft lip with or without palate (NSCLP) is common craniofacial anomalies. About 70% of cleft lip with or without palate is non-syndromic. These individuals are reported to have high prevalence of dental anomalies and studies suggested that the development of NSCLP and dental anomalies were contributed by MSX1 gene polymorphism. The aim of this study was to determine the prevalence of dental anomalies and MSX1 gene 799G>T polymorphism. The association between MSX1 gene 799G>T polymorphism with NSCLP as well as hyopodontia compared to non-cleft children were also determined. A comparative cross sectional study was carried out at Hospital Universiti Sains Malaysia from September 2014 to September 2015. The informed consent was obtained from all subjects. Clinical oral examination for 37 NSCL±P and 80 non-cleft children aged 7 to 13 years old were done followed by the orthopantomogram. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used in this study to identify the polymorphism. The buccal cells were collected from the subjects for genomic DNA extraction. Polymerase chain reaction (PCR) was used to amplify the partial part of MSX1 exon 2 by using one set of primer. The PCR product which could not be analyzed by PCR-RFLP was sent to DNA sequencing analysis to identify the polymorphism. The data were analyzed using IBM SPSS version 22.0. In the current study, male outnumbered female. UCLP (51.4%) was the common type of the cleft and the majority of the patients were presented with left side CLP (32.4%). The prevalence of dental anomalies in morphology in NSCL±P was 18.9% (95% CI: 5.7, 32.2) and non-cleft was 6.3% (95% CI: 0.8, 11.7). Hypodontia in NSCLP was 75% (95% CI: 61.2, 90.2) and non-cleft was 7.5% (95% CI: 1.6, 13.4). However, there was no rare polymorphism of 799G>T gene, all samples (n=117) contained common polymorphism 799G. Therefore, MSX1 799G>T polymorphism was not associated with NSCL±P and hypodontia. There was a significant association between NSCLP and dental anomalies in morphology (p=0.04) and number (p<0.01). The risk of having dental anomalies in morphology in NSCL±P children was 3.5 times and in number was 40 times more than non-cleft children. In conclusion, the prevalence of dental anomalies in morphology and number was very high in NSCL±P compared to noncleft children. However, it was not significantly associated with MSX1 799G>T polymorphism. It is recommended that a comprehensive oral healthcare program is essential to overcome the impacts of these dental anomalies to NSCL±P children.